Information systems concepts for management - Lucas, Henry C. (New York : McGraw-Hill, 1990)
The book is to help students and managers of management learn about the concepts of computer-based information systems
Includes index.
Bibliography: p. 421-424.
gp. 29/07/2019
loan
Keywords: Management information systems